(untitled) (Revista Apotheke, 2022)
These are writings about paths. In those paths, there is a need for forces. That need echoes potencies which, in times of crisis, provoke investment into collective actions that are capable of moving bodies out of formatted existences. Thus Uivo (howl) is born, as a heterogeneous pack that studies and researches philosophies of difference in art, in creation, in life. The forces that give birth to these howls come from unleashing our madness - which couldn’t stand to exist alone, and flung themselves into the wind in order to touch something/someone. By the potency of these affections, which are exploited by speech, writing, images, artistic actions and territorial displacements, other winds are contaminated. This requires a connection of forces to affect and to be affected, for affect is a force that is exerted on another. Force that is not violence, force that causes movement, that puts thought in motion, that allows things to acquire soul, provoking an augment in existence.